THE DEVELOPMENT OF ECOTOURISM CENTER ON CREATIVE ECONOMY IN ORNAMENTAL FISH INDUSTRY USING CAPITAL COMMUNITY-BASED PARTICIPATORY APPROACH - วงศ์อินทร์อยู่, กนกพัชร; สุขเจริญพงษ์, สมพล; ดิฐสถาพรเจริญ, ศานติ (RMUTT Global Business and Economics Review, 2015)
The purpose of this research was to develop Eco-tourism attraction based on Participating Community Based System under the Creative Economy Guidelines of ornamental fish industry of Thailand. Data were collected from: 1) 30 participants who were Siamese fighting fish farmers in Nong Pak Long Sub-district in Nakhon Pathom, Gold fish farmers in Nong Kob Sub-district in Ratchaburi, Gubby fish farmers in Takram-En Sub-district in Kanchanaburi, community representatives, and concerned officials and 2) 400 samples of tourists visiting the mentioned areas. Mixed methods research was used in the study. Qualitative data were collected by using in-depth interview and focus-group discussion. Meanwhile, questionnaires were distributed in order to gather quantitative data. Then, correlation analysis was performed to measure relationship of the problems addressed in the study. The findings revealed that: 1. the community context, economic community grants and social community grants of the three villages were similar. The average household of ornamental fish culture was 54. Each household had been cultured ornamental fish for a long time and they were good at farming ornamental fish for exporting as well, 2. the development of Eco-tourism attraction, “Ornamental Fish Villages” and the “Ornamental Fish Learning Center Models” of 3 provinces was done by 9 steps: 1) evaluating and concluding the information on building the “Ornamental Fish Villages” from the highest potential ornamental fish farm of the mentioned provinces; 2) organizing the committees for operating the “Ornamental Fish Villages”; 3) studying the designs of eco-tourism attraction from different areas in order to apply to build the “Ornamental Fish Villages”; 4) investigating the necessary needed things for building the “Ornamental Fish Villages”; 5) making the models of the “Ornamental Fish Villages”; 6) building the “Ornamental Fish Villages”; 7) making managing guidelines for developing the “Ornamental Fish Villages”; 8) training the little guides of the villages; and 9) making a promotion.